Teachers’ Beliefs Regarding Their Roles in Teaching English Listening Online: A Story from Two University Teachers in Indonesia - Hustarna Hustarna; Mursid Saleh; Sri Wuli Fitriati; Zulfa Sakhiyya (International Conference on Science, Education, and Technology, 2021)
Beliefs are part of cognition that significantly determine what and how teachers do in their classroom. This study employed a case study to investigate university teachers' beliefs regarding their roles in teaching English listening online. We involved two English listening teachers teaching at a university in Indonesia. The instruments used in this study were an interview and observations. The thematic analysis result of this study reveals that the two teachers have different beliefs about their roles in teaching English listening online. Teacher A believed that she should play roles as a facilitator, a manager, and a motivator. In contrast, teacher B stated that in online listening teaching, the roles he played were as an instructor and a counsellor. In addition, teacher A's beliefs align with her teaching practice, while teacher B's beliefs are incongruent with his teaching practice. Some factors contribute to this mismatch. Finally, recommendations are made for the betterment of online listening instruction